Influência da hierarquização da assistência obstétrica e neonatal na região da DIR XI SP no resultado materno e perinatal, período de 1995-2002 - Rudge, Marilza Vieira Cunha [UNESP]; Maestá, Izildinha [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Rudge, Cibele Vieira Cunha [UNESP]; Anzai, Álvaro [UNESP]; Gushikem, Érica [UNESP]; Conceição, Jane Amanda Jeronymo da [UNESP]; Santos, Camila Rebouças Valência dos [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
General Objective: to evaluate the influence of the Delivery and Newborn Assistance Hierarchyzation Program on maternal and perinatal results in the DIR XI –SP region, from 1995 to 2002. Specific Objectives: to calculate the number of deliveries, Caesarean rates, the cause of hospitalar maternal mortality (HMMC) and precocious perinatal mortality rates (PPMR), in maternity hospitals of low risk (Hospital Regional-Associação Beneficente dos Hospitais Sorocabana – HR-ABHS) and high risk (Hospital das Clínicas da Faculdade de Medicina de Botucatu – UNESP – HC-FMB). Methodology: descriptive and prospective study of hierarchyzation in delivery and newborn assistance, during eight years (1995-2002), in low risk (HR-ABHS) and high risk (HC-FMB) hospitals in the DIR XI region. The study included all the patients attended at these Services with daily record of standardized clinical protocol containing the following information: number of deliveries, Caesareans, maternal deaths, liveborns, stillborns and precocious neoborns (up to 7 days of age). The ?2 test and the calculus of simple linear correlation coefficient were used to assess the results. Results: the total of assisted deliveries in that period was 17748, being that, at the program settlement time, 410 deliveries/year at HR-ABHS and 1076/year at HC-FMB were performed. There was an increase of 2.5 times in the number of deliveries in low risk hospitals and, in high risk hospitals, that number was maintained. The number of deliveries in 2002 was similar for both Services. Caesarean rate decreased in both places, however, it was more accentuated in the low risk (HR-ABHS from 46.6% to 26.9%; ? < 0.0001) than in the high risk hospital (HC-FMB from 49.2% to 40.1%; ? < 0.0001). HMMC was lower at HR-ABHS (26.3 vs 128.7 / 100,000 liveborns; ? < 0.02). PPMR decreased in both Services, with more accentuated fall in the high risk hospital (HC-FMB from 60.8‰ to 26.2‰; ? < 0.00001) than in the low risk one (HR-ABHS from 9.7‰ to 6.7‰; ? < 0.04). Conclusions: The Delivery and Newborn Assistance Hierarchyzation Program improved the obstetric and perinatal assistance quality in the DIR XI – SP region: there was a decrease in Caesarean and perinatal mortality rates in both hospitals. Maternal mortality was higher in the high risk hospital, however, during two years, no death occurred in the tertiary hospital. There was no maternal mortality in the secondary hospital during six years. The importance of delivery and newborn hierarchyzation levels was proved by the decrease of Caesarean rates associated to diminished perinatal I mortality rate.

Objetivo geral: avaliar a influência do Programa de Hierarquização da Assistência ao Parto e Recém-nascido no resultado materno e perinatal, na Região da DIR XI - SP, entre os anos de 1995 e 2002. Objetivos específicos: calcular o número de partos, taxas de cesárea, Razão de Mortalidade Materna hospitalar (RMMH) e taxas de Mortalidade Perinatal precoce (MPN I), nas maternidades de baixo (Hospital Regional - Associação Beneficente dos Hospitais Sorocabana – HR-ABHS) e alto risco (Hospital das Clínicas da Faculdade de Medicina de Botucatu – UNESP – HC-FMB). Metodologia: trabalho descritivo e prospectivo, da hierarquização no atendimento ao parto e ao recém-nascido, durante oito anos (1995-2002), em hospitais de baixo (HR-ABHS) e alto risco (HC-FMB), da região da DIR XI. Foram incluídas todas as pacientes atendidas nestes Serviços com registro diário de protocolo clínico padronizado com as seguintes informações: número de partos, cesáreas, mortes maternas, nativivos, natimortos e neomortos precoces (até 7 dias de vida). O teste do ?2 e o cálculo do coeficiente de correlação linear simples foram utilizados para avaliação dos resultados. Resultados: o total de partos assistidos no período foi de 17748, sendo que na implantação do programa eram realizados 410 partos / ano no HR-ABHS e 1076 partos / ano no HC-FMB. Houve aumento de 2,5 vezes no número de partos no hospital de baixo risco e manutenção do número de partos no alto risco. O número de partos em 2002 é semelhante nos dois Serviços. A taxa de cesárea declinou nos dois locais, porém, de forma mais acentuada no baixo risco (HR-ABHS de 46,6% para 26,9%; ? < 0,0001) que no alto risco (HC-FMB de 49,2% para 40,1%; ? < 0,0001). A RMMH foi menor no HR-ABHS (26,3 vs 128,7 / 100.000 nascidos vivos; ? < 0,02). A taxa de MPN I declinou nos dois serviços, com diminuição mais acentuada no alto risco (HC-FMB de 60,8‰ para 26,2‰; ? < 0,00001) do que no baixo risco (HR-ABHS de 9,7‰ para 6,7‰; ? < 0,04). Conclusões: o Programa de Hierarquização ao Parto e Recém-nascido melhorou a qualidade da assistência obstétrica e perinatal na região da DIR XI - SP: houve diminuição das taxas de cesárea e de mortalidade perinatal I nos dois hospitais. A morte materna foi mais freqüente no hospital de alto risco, mas durante dois anos não ocorreu nenhum óbito no hospital terciário. Não houve nenhum óbito materno no Hospital secundário durante seis anos. Comprovou-se a importância de níveis hierarquizados de assistência ao parto e recém-nascido, com a diminuição dos índices de cesárea associada à diminuição da taxa de mortalidade perinatal I.
Influence of hierarchyzation of obstetric and neonatal assistance in the DIR XI SP region on maternal and perinatal results from 1995 to 2002
Keywords: Hierarchyzation; Delivery assistance; Maternal and perinatal results; Biológicas; Saúde; Hierarquização; Assistência ao parto; Resultados maternos e perinatais